(untitled) (UNWE Yearbook, 2024)
The goal of this article is to study the impact of consumer loans volume and effective interest rate of consumer loans on gross fixed capital formation in Bulgaria. The survey is realized on the grounds of quarterly data during the period 2009-2023. The econometric methodology through which the data are processed includes: Stationarity Test; Vector Autoregressive (VAR) Model; Selection of the maximal lag; Cointegration Test; Vector Error Correction Model (VECM); Granger causality test. It is established: in long-term period 1% increase in consumer loans increase the volume of gross fixed capital formation with 0.94%; the coefficient value of ECTt-1 is 0.765, which means that approximately 77% of the discrepancy between long-term and short-term gross fixed capital formation is adjusted for a quarter; in short term there is bilateral causality between consumer loans and gross fixed capital formation and unidirectional causality from effective interest rate of consumer loans to gross fixed capital formation.